Effect of Chewing Xylitol Gum on Salivary Volume and Acidity - Alfonsa Angwarmase; Fen Tih; Meilinah Hidayat (Journal of Medicine and Health, 2017)
Dental caries or tooth decay is a result of the production of acid from fermentation ofbacteria that destroy tooth tissue. It can be prevented by maintaining the stability of salivaryvolume and acidity. Chewing xylitol gum is beneficial for increasing salivary volume andacidity. The aim of the study is to determine the effect of chewing xylitol gum on salivary volumeand acidity. The study is a quasi experiment conducted to 30 males aged between 17-25 yearsold. Pre and post treatmentâ€™s salivary volume are measured with measuring cup. Pre and posttreatmentâ€™s salivary acidity are measured using a pHmeter with 0,1 accuracy. Data areanalyzed with paired â€œtâ€ test (a = 0,05). Average salivary volume after chewing xylitol gumincreased very significantly from 0,26 mL to 13,37mL (p=0,000). Average salivary acidity afterchewing xylitol gum increased very significantyly from 6,47 to 7,36(p=0,000). The researchconcludes that chewing xylitol gum increases salivary volume and acidity.Keywords : dental caries, xylitol, salivary volume, salivary acidity